The genesis of the alkaline rock series of the benom complex, central belt of the peninsular Malaysia - Umor, M.R.; Abdul Ghani, A.; Mohamad, H. (2008)

(untitled)
The Genesis of the Benom Complex is important to reveal because of their history will give the whole view about the evolution of the Central Belt of the Peninsular Malaysia. In our study, we focused on the alkaline rock series of the Benom Complex. It is allocate as elongated body by the trend north-south at the western hill of Mount Benom. This series consists of gabbro, pyroxenite, diorite, syenite, and monzonite with the lesser amount of dolerite dykes and mafic microgranular enclaves. It was predominantly high-K, shoshonitic series with I-type characteristics. It was metaluminous and classified as the magnesium pluton. They have very high total alkaline and LIL elements, i.e. Ba and Sr. Based on geochemical studied, we postulated that the genesis of the alkaline rock series in the Benom Complex can be explained by the model of the slab breakoff.